Concurrence of hemophagocytic lymphohistiocytosis and small-cell lung cancer in bone marrow: A case report and literature review. (March 2022) - Xu, Wenyan; Guo, Zhenxing
Hemophagocytic lymphohistiocytosis is a rare and almost universally fatal disease in adults. A 60-year-old female patient presented to our hospital with a 3-day history of weakness and anorexia. Physical examination revealed severe pallor without lymphadenopathy or hepatosplenomegaly. The initial blood test showed a hemoglobin level of 2.6 g/dL and a platelet count of 76 × 10 9 /L. Later the patient experienced persistent high fever for 1 week without any obvious infective symptoms. Biochemical examination revealed hyperferritinemia and low natural killer cell viability. The bone marrow morphology showed hemophagocytosis and infiltration with metastatic small-cell lung cancer. The patient was diagnosed as small-cell lung cancer-related hemophagocytic lymphohistiocytosis. Subsequently, she underwent chemotherapy with dexamethasone and etoposide. However, the patient succumbed within 2 weeks of presentation due to rapidly progressive disease. In conclusion, we reported the first hemophagocytic lymphohistiocytosis case with small-cell lung cancer. It is critical to have early identification of hemophagocytic lymphohistiocytosis in patients with small-cell lung cancer.